Business Intelligence Technology and Marketing Strategy in the Retail Sector - Owuor, Ezekiel Ochieng; Njeru, Winnie (Advances in Social Sciences Research Journal, 2018)
Today’s world is undergoing unprecedented changes due to increased competition, globalization, demanding customers with diverse tastes and preferences. This growth could be attributed to the declining cost of acquiring and storing very large amounts of data arising from sources such as customer transactions in retail outlets, e-businesses, RFID tags for inventory tracking, email, and product reviews among others. Business Intelligence technology is a recent development in business decision-making, both strategic and tactical, and a key driver of profitability. Critical corporate decisions are now grounded on empirical data which constitute the basis of both descriptive and predictive analytics. The study sought to assess the influence of Business Intelligence technology on marketing strategies of large supermarkets in Nairobi. Supermarkets generate vast amounts of transactional data, which can comprise a source of value when appropriate BI technology is optimally deployed on them to extract potentially strategic information. The study targeted five large supermarkets. The study used a descriptive cross-sectional research design where a structured questionnaire was used to collect pertinent data. Data were analysed using descriptive statistics and logistic regression analysis. The study results indicated minimal use of BI technology by large supermarkets in Nairobi county hence the influence of the same on marketing strategies was not extensive. However, the study established a statistically significant influence of certain aspects of BI technology on marketing strategy of large supermarkets in Nairobi. Despite lack of access to such data, supermarkets employed other components of BI technology such as data warehousing and market basket analysis which were used to some extent for market segmentation. The study recommends that supermarkets should widen their range of BI technologies and sources of data in order to enhance their marketing strategies. The study can be replicated in other service industries.